2000
DOI: 10.1051/forest:2000163
|View full text |Cite
|
Sign up to set email alerts
|

Canopy uptake of N deposition in spruce (Picea abies L. Karst) stands

Abstract: -In order to quantify the total deposition and canopy uptake of N in spruce, plastic Christmas trees were established next to real spruce trees of approximately similar height in clearings of the Strengbach catchment (Vosges mountains, France). Bulk precipitation and throughfall (TF) composition under the artificial trees, the real spruce trees, and in 3 spruce stands aged 15, 35 and 90 years were monitored during 8.5 months. Fluxes of inorganic N, SO 4 2-and Na + in throughfall below plastic trees were 50% (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 26 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…forest ecosystems (2 to 8%: Boyce et al 1996;up to 5%: Wilson & Tiley 1998). Similarly, as found for aquatic (Touchette & Burkholder 2000) and terrestrial (Wilson 1992, Peuke et al 1998, Ignatova & Dambrine 2000 angiosperms and marine algae (Lotze & Schramm 2000), we found that foliar uptake is generally higher for NH 4 + than for NO 3 -. A linear increase in the uptake rate (Figs.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…forest ecosystems (2 to 8%: Boyce et al 1996;up to 5%: Wilson & Tiley 1998). Similarly, as found for aquatic (Touchette & Burkholder 2000) and terrestrial (Wilson 1992, Peuke et al 1998, Ignatova & Dambrine 2000 angiosperms and marine algae (Lotze & Schramm 2000), we found that foliar uptake is generally higher for NH 4 + than for NO 3 -. A linear increase in the uptake rate (Figs.…”
Section: Discussionmentioning
confidence: 49%
“…Although leaching and the presence of epiphytic macroflora complicates interpretation of throughfall studies (Pearson & Stewardt 1993), it is also evident in terrestrial systems that foliar N-uptake is generally more efficient for NH 4 + than for NO 3 - (Wilson 1992, Peuke et al 1998, Ignatova & Dambrine 2000. In this study, we address the question as to the extent in which foliar uptake of nitrogen contributes to the nutrient demand of halophytic species that grow in the lowest areas of tidal salt marshes.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…As indicated by the positive coeffi cient of C x for Ca 2+ and Mg 2+ , the two ions show the signifi cant canopy leaching increased with the concentrations in precipitation during the growing seasons of spring and summer ( Ignatovaa and étienne (2000) found that the canopy uptake of nitrogen deposition was higher in young, fastgrowing stands that had a high N requirement compared with the old and poorly growing stands. Christ et al (1995) and Brumme et al (1999) reported that the increasing NH 4 + concentration in precipitation was accompanied by the increasing retention of NH 4 + , which was similar to our present study.…”
Section: Ion Concentration and Precipitation Aciditymentioning
confidence: 95%
“…It could be shown that high atmospheric nitrogen input has a depressive effect on tree vitality during dry periods [7]. Furthermore, a Norway spruce canopy can uptake especially NH 4 + nitrogen directly from the atmosphere [12]. This makes it more difficult for a balanced nutrient composition of the tree.…”
Section: Discussionmentioning
confidence: 99%